Kebijakan Adaptasi Perubahan Iklim Bidang Pertanian - Dila Novita (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2018)
Strengthening capacity of agricultural extension workers is the significant strategy in attempt to overcome climate change impact therefore, Indonesian Ministry of Agriculture in collaboration with Japan International Cooperation Agency (JICA) developed an adaptation and mitigation program of climate change by doing Training of Trainers (ToT) for the agricultural extension workers who obligated to continue the skills and materials to farmers and colleagues in their regions. Aims of this research:1. Understanding participants assessment of ToT on adaptation strategy of climate change for agricultural extension workers in Jeneponto district, South Sulawesi, 2. Analizing participant’s assessment to materials and speakers. This research applied mix-methods (quantitative and qualitative) by doing survey and observation. Research findings: 1) Participants gave positive evaluation to organization of ToT due to this program is a new strategy to cope with the climate change impact. 2) Participants gave high score (4 or 5) to all materials with positive response to the speakers who deliver the materials by using tools as well as field practice.